Understanding of SOCIO-PSYCHOLOGICAL ASPECT OF ATTITUDE OF YOUNG PEOPLE TO THE CRIMINALITY PROBLEM - Kryvolapchuk, Volodymyr; Kulyk, Olexandr; Nemesh, Olena; Kocharian, Alexander; Barinova, Natalia (International Journal of Psychosocial Rehabilitation, 2020)
The research paper contains key findings of the random monitoring survey of the Kyiv students covering the period 2002-2017, in the course of which it was explored what is the attitude of young people to the problems of crime and the police’s activities aimed at counteracting it in the city. The survey was conducted annually in 4 to 5 higher education institutions of the city. Sampling was two-tiered, random and based on the principle of maintaining the distribution quota of the Kyiv universities’ students with respect to sex and age. The applied survey method was filling in the questionnaires by the respondents. The average annual number of the respondents was 481 individuals. The analysis of the survey findings allowed to identify the level of students’ fear to become victims of certain types of crime, a degree of their victimization in general and their fear to suffer from particular crimes, their assessments of the character of crime dynamics in the city and the police’s activities, to learn the opinions on the situation with personal security at a given time and in future. Among the trends identified in the course of the research are a high level of the respondents’ fear to become a victim of violent and most spread minor offences; high level of their victimization that distinctly decreased in recent years; prevailing negative assessments of the crime dynamics, assessment of the police’s activities and trust to it as unsatisfactory irrespective of the improvements in these indicators in the recent three years, prevailing negative assessment of the situation with personal security and on the whole, positive expectations in relation to the changes in future.